2020
DOI: 10.15376/biores.15.3.6344-6370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of torrefaction temperature and O2 concentration on the pyrolysis behaviour of moso bamboo

Abstract: Five-year-old moso bamboo was torrefied under nitrogen and different oxygen concentrations of 3% to 9% and torrefaction temperatures of 200 °C to 300 °C. Mass yields of 31.7% to 96.6%, energy yields of 30.8% to 98.9%, and higher heating values (HHVs) in the range 18.8 to 27.1 MJ/kg were obtained. The torrefied sample was characterized by Fourier transform infrared spectrometry (FTIR). Under the different torrefaction temperatures and oxygen concentrations, hemicellulose and cellulose were thermally decomposed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Contrary to this popular view, Basu et al reported that the effect of oxygen concentration on the calorific value of torrefied biomass products is marginal [27]. Sun et al reported that torrefaction temperature and oxygen concentration significantly influenced bamboo pyrolysis [28].…”
Section: Introductionmentioning
confidence: 94%
“…Contrary to this popular view, Basu et al reported that the effect of oxygen concentration on the calorific value of torrefied biomass products is marginal [27]. Sun et al reported that torrefaction temperature and oxygen concentration significantly influenced bamboo pyrolysis [28].…”
Section: Introductionmentioning
confidence: 94%
“…Basu et al reported that the effect of oxygen concentration on the heating value of a torrefied biomass product is marginal [ 23 ]. Otherwise, Sun et al reported that torrefaction temperatures and oxygen concentrations remarkably influenced the pyrolysis of bamboo [ 26 ]. Wang et al [ 27 ] reported moderate and severe removal of hemicellulose can be achieved through torrefaction under air and nitrogen, respectively.…”
Section: Introductionmentioning
confidence: 99%